Designing polymer conjugates as lysosomotropic nanomedicines. (22nd January 2007) - Duncan, R.
Abstract : Marriage of cell biology (the concept of 'lysosomotropic drug delivery') and the realization that water-soluble synthetic polymers might provide an ideal platform for targeted drug delivery led to the first synthetic polymer–drug conjugates that entered clinical trials as anticancer agents. Conceptually, polymer conjugates share many features with other macromolecular drugs, but they have the added advantage of the versatility of synthetic chemistry that allows tailoring of molecular mass and addition of biomimetic features. Conjugate characteristics must be optimized carefully to ensure that the polymeric carrier is biocompatible and that the polymer molecular mass enables tumour-selective targeting followed by endocytic internalization. The polymer–drug linker must be stable in transit, but be degraded at an optimal rate intracellularly to liberate active drug. Our early studies designed two HPMA [ N -(2-hydroxypropyl)methacrylamide] copolymer conjugates containing doxorubicin that became the first synthetic polymer–drug conjugates to be tested in phase I/II clinical trials. Since, a further four HPMA copolymer–anticancer drug conjugates (most recently polymer platinates) and the first polymer-based γ-camera imaging agents followed. Polymer–drug linkers cleaved by lysosomal thiol-dependent proteases and the reduced pH of endosomes and lysosomes have been used widely to facilitate drug liberation. It is becoming clear that inappropriate trafficking and/or malfunction of enzymatic activation can lead to new mechanisms of clinical resistance. Recent studies have described HPMA copolymer conjugates carrying a combination of both endocrine and chemotherapy that are markedly more active than individual conjugates carrying a single drug. Moreover, current research is investigating novel dendritic polymer architectures and novel biodegradable polymers as drug carriers that will provide improved drug delivery and imaging probes in the future. The present paper reviews the clinical status of polymeric anticancer agents, the rationale for the design of polymer therapeutics and discusses the benefits and challenges of lysosomotropic delivery.